Genetic Variability and Its Implications on Early Generation Sorghum Lines Selection for Yield, Yield Contributing Traits, and Resistance to Sorghum Midge - Massaoudou Hamidou; Abdoul Kader M. Souley; Issoufou Kapran; Oumarou Souleymane; Eric Yirenkyi Danquah; Kwadwo Ofori; Vernon Gracen; Malick N. Ba (International Journal of Agronomy)
Sorghum is the second most important cereal crop in Niger. The crop is grown in a wide range of ecological environments in the country. However, sorghum grain yield in Niger is limited by both abiotic and biotic constraints. Recombinant inbred lines derived from the cross of a local variety with a midge resistant variety and two local checks were evaluated during the 2015 rainy season across two planting dates in two environments in Niger. The objective was to investigate genetic variability for yield, yield related traits, and resistance to sorghum midge. High phenotypic coefficient of variation (PCV) versus genotypic coefficient of variation (GCV) was observed in both sites and planting dates. Across planting dates at both Konni and Maradi, grain yield, plant height, panicle weight, and midge damage had high heritability coupled with high estimates of genetic advance. At Konni, high genetic advance coupled with high heritability was detected for grain yield, plant height, panicle weight, and resistance to midge. There were similar results at Maradi for grain yield, plant height, and panicle weight. Therefore, selection might be successful for the above characters in their respective environments.